2018
DOI: 10.1097/md.0000000000010472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ω-3 polyunsaturated fatty acid-supplemented parenteral nutrition on inflammatory and immune function in postoperative patients with gastrointestinal malignancy

Abstract: Background: There are no consensus regarding the efficacy of omega-3polyunsaturated fatty acids (PUFAs) on inflammatory and immune function in postoperative patients with gastrointestinal malignancy.Methods:The literatures published randomized control trials (RCT) were searched in PubMed, Embase, Scopus, Cochrane Library, CNKI, Weipu, and Wanfang Databases. The immune efficacy outcomes of ω-3 polyunsaturated fatty acid-supplemented parenteral nutrition in patients with gastrointestinal malignancy were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 21 publications
3
37
0
4
Order By: Relevance
“…However, flaxseed oil administration in sheep infected with F. hepatica did not affect production or gene expression of IL-4 and interferon-γ (14) . Similar to our findings, Zhao & Wang (34) found that n-3 fatty acids applied as a part of parenteral nutrition in postoperative patients with gastrointestinal malignancy decreased CRP and other inflammatory markers. An in vitro study demonstrated that peripheral blood lymphocytes of women with GDM when exposed to n-3 fatty acids caused elevated GSH and decreased MDA cell levels (35) .…”
Section: Effects On Biomarkers Of Inflammation and Oxidative Stresssupporting
confidence: 91%
“…However, flaxseed oil administration in sheep infected with F. hepatica did not affect production or gene expression of IL-4 and interferon-γ (14) . Similar to our findings, Zhao & Wang (34) found that n-3 fatty acids applied as a part of parenteral nutrition in postoperative patients with gastrointestinal malignancy decreased CRP and other inflammatory markers. An in vitro study demonstrated that peripheral blood lymphocytes of women with GDM when exposed to n-3 fatty acids caused elevated GSH and decreased MDA cell levels (35) .…”
Section: Effects On Biomarkers Of Inflammation and Oxidative Stresssupporting
confidence: 91%
“…C18:1 as the most abundant MUFA in the adipose and muscle tissues of ruminants, and it is not easily susceptible to oxidation [29]. PUFA are further divided into four families: omega-3 (n-3), omega-6 (n-6), omega-7 (n-7) and omega-9 (n-9), based on the position of the initial double bond on the methyl terminal [30] or the location of the last double bond relative to the terminal methyl end of the molecule [31].…”
Section: Fatty Acids Classifications and Functionsmentioning
confidence: 99%
“…Zhang et al 30 found that ω-3 PUFA-supplemented PN could improve postoperative recovery, reduced postoperative complications, and shorten hospital stays after hepatectomy in patients with liver cirrhosis or liver cancer. A meta-analysis by Zhao et al 31 revealed that early application of ω-3 PUFAs in patients with gastrointestinal cancer could improve immunity, reduce the postoperative stress response, and attenuate metastasis or recurrence. However, other studies have shown that there is no signi cant correlation between ω-3 PUFAs and postoperative complications in colorectal or esophageal cancer patients 12,32−33 .…”
Section: Discussionmentioning
confidence: 99%